The redox behavior of rare earth elements - Cicconi, Maria Rita; Le Losq, Charles; Henderson, Grant S.; Neuville, Daniel R. (Magma Redox Geochemistry, 2021)
Elements in the lanthanides series are usually known under the name of rare earth elements (REE). In past decades, the use of these elements in industrial processes has increased exponentially with the development of novel technologies and applications. In addition to such growing industrial importance, and despite their relatively low concentrations in the Earth system, REE are sensitive markers of crystal-melt equilibria in geological systems. As a result, the study of lanthanides in materials, either as whole group or as single species, has become an important point of focus in both Geo- and Materials Sciences. Among REE, Ce and Eu are stable in many geological environments, with two different oxidation states (Ce 3+ /Ce 4+ and Eu 2+ /Eu 3+ ), hence, these two redox couples have been proposed as proxies for oxygen fugacity ( f O 2 ) in different environments (oxybarometer). However, it is essential to understand the factors influencing redox mechanisms in order to use Ce/Eu distribution as f O 2 sensors. In this chapter, we present an overview of REE properties in minerals, melts, and glasses, and illustrate their importance through examples of applications in the fields of geochemistry, petrology, and mineralogy.
Created from Fastlane, Scopus look-up
Keywords: Cerium; Europium; Oxybarometers; Silicate melts; Trace elements